Cultivating Character in The Digital Age: Umar Ibn Ahmad Bārājā's Moral Education Framework for Society 5.0 - Muntakhib, Ahmad; Mustolehudin, Mustolehudin; Taruna, Mulyani Mudis; Dahri, Harpandi (Analisa: Journal of Social Science and Religion, 2024)
The era of society 5.0 provides new challenges for Islamic education, especially in moral education. One of the scholars who has great attention to moral education is Umar Ibn Ahmad Bārajā. This study seeks to describe and analyze the thoughts of Umar Ibn Ahmad Bārajā in the books Akhlaq li al-Banin and Akhlak li al-Banat on moral education which is very interesting to be projected in the era of society 5.0. The focus raised is how moral education from the perspective of Umar Ibn Ahmad Bārajā, the values contained in moral education and Umar Ibn Ahmad Bārajā's moral education strategy in the era of Society 5.0. This research is a qualitative study with a research focus on the thoughts of Umar Ibn Ahmad Bārajā in the books Akhlaq li al-Banin and Akhlak li al-Banat. This thought is analyzed by content analysis and then projected in the era of Society 5.0. There are three research findings. First, good morals must begin to be built in education carried out by families that are strengthened by educational institutions. Second, the values instilled are respecting and honoring both parents, teachers, all elders, Honest in speaking, Tawadlu', Patience, Not avoiding each other, Not quarreling, and Not raising your voice when talking or laughing. Third, the use of gender-based names, habits, homework and role modeling.